The effect of unified rhythmic activity on psychological factors among girls with mild intellectual disability: A randomized controlled trial - Vinolia Baskara Seliyan; Mary Glory Ponrani Mohanraj; Josyula Tejaswi; Vinu Wilson; Parveen Kumar; Debajit Karmakar; Yuni Astuti (Journal of Coaching and Sports Science, 2026)
Background: Girls with mild intellectual disability experience persistent deficits in adaptive behavior, coping skills, and social integration, particularly during adolescence when psychosocial demands intensify. Despite this need, accessible, school-based psychological interventions remain limited. Given the risk of long-term social exclusion and reduced quality of life, identifying low-cost, inclusive strategies such as unified rhythmic activity is urgently required. Aims: This study evaluated the effects of rhythmic activity training and unified rhythmic activity training on psychological outcomes, adaptive behavior, and coping strategies for girls with MID, who participated alongside typically developing peers. Methods: A three-arm randomized controlled trial included 45 girls (10–14 years) with mild intellectual disability (IQ 50–70) in Coimbatore, India. Participants were assigned to rhythmic training, unified rhythmic training, or control groups. Interventions lasted 12 weeks (60 minutes, thrice weekly). Primary outcomes were adaptive behavior and coping strategies; secondary outcomes included self-efficacy, social competence, emotional regulation, quality of life, and behavioral problems. Analyses applied intention-to-treat, repeated measures ANOVA, and ANCOVA. Result: Significant within-group reductions were found for Irritability/Agitation in RATG and URATG (both p < 0.001), but not in CG (p = 0.64), with significant between-group differences (p < 0.001). Social Withdrawal improved in RATG (p = 0.003) and URATG (p < 0.001), not in CG (p = 0.81). Stereotypic Behavior and Hyperactivity decreased significantly in both intervention groups (p ≤ 0.009), but not in CG (p ≥ 0.75), with significant group effects (p < 0.001). Inappropriate Speech showed no within-group significance, though between-group differences were significant (p = 0.001). Conclusion: This study establishes that rhythmic and unified rhythmic interventions significantly enhance adaptive behavior and coping in girls with mild intellectual disability, with the unified model offering superior social benefits. It advances inclusive physical activity as a theoretically grounded, evidence-based approach and contributes robust experimental data supporting scalable, school-based psychosocial interventions.